Tracking health sector priority setting processes and outcomes for human resources for health, five-years after political devolution: A county-level case study in Kenya - Munywoki, J; Kagwanja, N; Chuma, J; Nzinga, J; Barasa, E; Tsofa, B (BioMed Central, 2020)
Background: Health sector priority setting in Low and Middle-Income Countries (LMICs) entails balancing between a high demand and low supply of scarce resources. Human Resources for Health (HRH) consume the largest allocation of health sector resources in LMICs. Health sector decentralization continues to be promoted for its perceived ability to improve efficiency, relevance and participation in health sector priority setting. Following the 2013 devolution in Kenya, both health service delivery and human resource management were decentralized to county level. Little is known about priority setting practices and outcomes of HRH within decentralized health systems in LMICs. Our study sought to examine if and how the Kenyan devolution has improved health sector priority setting practices and outcomes for HRH.